Immune enhancement of pulmonary clearance of nontypable Haemophilus influenzae. - Hansen, E J (1988)
BALB/c mice systemically immunized by intraperitoneal injection with whole, viable cells of two different strains of nontypable Haemophilus influenzae (NTHI) exhibited a markedly enhanced ability to clear the homologous strain of NTHI from the lower respiratory tract. Immunization did not influence the number of phagocytic cells recovered by bronchoalveolar lavage from mice before or after intrapulmonary challenge with NTHI. Immunization also induced the synthesis of relatively large quantities of NTHI-directed antibodies which were detectable in both the bloodstream and the alveolar spaces of the lung. Radioimmunoprecipitation and Western blot (immunoblot) analyses indicated that these antibodies were directed against both the proteins and lipooligosaccharide (LOS) in the NTHI outer membrane. Bactericidal and opsonophagocytic assays determined that the NTHI-directed antibodies in the serum were functional and able to kill or opsonize the homologous NTHI strain. Mice immunized with an NTHI major outer membrane protein-LOS complex also had an increased ability to effect pulmonary clearance of NTHI. Serum and bronchoalveolar lavage fluid collected from these animals immunized with the outer membrane protein-LOS complex contained relatively high levels of antibodies to both of these antigens. The serum from these animals also possessed bactericidal and opsonic activity against the homologous NTHI strain. These results indicate that systemic immunization can enhance the ability of experimental animals to clear NTHI from the lower respiratory tract and suggest that immunoprophylaxis of NTHI pulmonary disease may be feasible.